2020
DOI: 10.26444/aaem/110770
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional intelligence in attitudes towards elderly patients – Comparative study of medical students from rural and urban areas

Abstract: Introduction. Medical care in geriatrics has its own specificity, and in order to build a successful doctor-patient relationship it is important while studying medicine to learn some functioning aspects of this age group. Objective. The aim of this study is to explore and describe the role of emotional intelligence in the attitudes of medical students towards elderly patients, taking into account their the place of residence. The place of residence has an impact on social relations and socialization, which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…which stated the attitude towards elderly was determined by emotional intelligence as well as place residency. 24 This was later supported by Karamivand et. al.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…which stated the attitude towards elderly was determined by emotional intelligence as well as place residency. 24 This was later supported by Karamivand et. al.…”
Section: Discussionmentioning
confidence: 71%
“…28,29 As a result, younger generations are being more independent and living far away from generational families which causes reduction in contact with elderly. 24 In other words, there is a probability that those students in rural areas have higher knowledge and attitude because they are closer to their elders than those from urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, courses addressing the handling of complexity and focusing on motivation and attitudes regarding caring for older adults might be more promising than knowledge-based education. This is supported by studies among nursing and medical students which found that correcting false beliefs about older people, focusing on empathybuilding and enhancing a better understanding of the ageing process made them more positive about and confident in treating older patients [16,18,19,[52][53][54][55]. To support the building of care networks and strengthen a comprehensive understanding of the very old patient, broadly including the relevant areas for maintaining autonomy and well-being, this training could be provided in an interdisciplinary setting.…”
Section: Discussionmentioning
confidence: 97%